Legal Responsibility of Marketplaces in Online Buying and Selling Transactions in Indonesia: An Analysis of the Effectiveness of Digital Consumer Protection - Ibnu Sina Nur Ubay; Reza Saputra; Harmono Harmono; Jaenudin Umar (Ann Publisher, 2026)
Background. This study analyzes the effectiveness of consumer protection regulations in online buying and selling transactions in Indonesia by highlighting the gap between normative legal certainty and real protection experienced by consumers in the digital marketplace ecosystem. The scope of the study includes the implementation of consumer protection laws in e-commerce transactions as well as structural, institutional, and sociological factors that hinder their effectiveness. Aims. The research aims to critically examine the application of the applicable legal framework in practice and to identify systemic causes of repeated violations, such as mismatches in goods, misleading product information, and limitations in consumer rights recovery mechanisms. Method. The method used is normative legal research, drawing on legislative, conceptual, and analytical-critical approaches. Primary legal materials consist of laws and regulations related to consumer protection and electronic transactions, supported by secondary legal materials from reputable international journals, OECD and UNCTAD reports, and documentation of consumer complaints over the last five years. Data were collected through literature review and document analysis, with validation using source triangulation and theory. Results. The results of the study show that although the normative framework for consumer protection in Indonesia is relatively comprehensive, its implementation in e-commerce remains weak due to weak law enforcement, low consumer legal literacy, fragmentation of responsibilities among digital business actors, and regulatory ambiguity regarding the role of marketplaces. Conclusion. Using Legal System Theory, information asymmetry, contractual justice, and economic analysis of the law, this study concludes that consumer protection remains dominant in the books but has not fully functioned in practice. Implementation. It is necessary to strengthen market accountability, simplify digital dispute-resolution mechanisms, and increase consumer legal literacy.